Cracks width prediction of steel-FRP bars reinforced high-strength composite concrete beams. (September 2022) - Wang, Lei; Fan, Langbo; Fu, Feng; Song, Zhaoping
Abstract: To study the crack development of composite steel-FRP rebar reinforced (SFCB) high strength concrete beams, a bending test of this type of beams is performed. The test shows that crack width of the SFCB beam is in between steel reinforced beam and the CFRP reinforced beam using same reinforcement ratio. The crack width of SFCB test beams is 47.9% larger than that of steel reinforced beams and 38.7% smaller than that of CFRP reinforced beams. When the steel core ratio increased from 18.37% to 32.65%, the crack width decreased by 16.5% on average before steel core yielding. After the steel core yielded, the crack width of the H-SF-3, 4 beamincreased at an accelerated rate. The crack width of the latter increased by 13.7% on average compared with the former. Based on test results, a new formula for calculating crack width of SFCB reinforced concrete is established, it considers the material properties of SFCB, the degradation of elastic modulus of the SFCB steel core after yielding and the compatibility of 3 different materials. It introduces a bond reduction coefficient vi of SFCB and concrete and the compatibility coefficient st of the steel core and fibre layer, This formula can accurately predict the maximum crack width of SFCB reinforced concrete beams.